2015
DOI: 10.3174/ajnr.a4314
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Virtual Monochromatic Images for Evaluation of Normal Tissues and Head and Neck Cancer Using Dual-Energy CT

Abstract: BACKGROUND AND PURPOSE: Dual-energy CT is not used routinely for evaluation of the head and neck, and there is no consensus on the optimal virtual monochromatic image energies for evaluating normal tissues or head and neck cancer. We performed a quantitative evaluation to determine the optimal virtual monochromatic images for visualization of normal tissues, head and neck squamous cell carcinoma, and lymphadenopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
47
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 91 publications
(56 citation statements)
references
References 22 publications
(25 reference statements)
7
47
0
2
Order By: Relevance
“…The reason was explained by the fact that a hypervascular tumor takes up iodine more than the OARs such as brainstem and spinal cord . Lam et al demonstrated that the tumor attenuation of the primary tumor for the HNC was highest in the VMI 40 keV (207.9 ± 46.8 HU) . A similar CT number was observed in the VMI 40 keV for the CTVb in this study (Table ).…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…The reason was explained by the fact that a hypervascular tumor takes up iodine more than the OARs such as brainstem and spinal cord . Lam et al demonstrated that the tumor attenuation of the primary tumor for the HNC was highest in the VMI 40 keV (207.9 ± 46.8 HU) . A similar CT number was observed in the VMI 40 keV for the CTVb in this study (Table ).…”
Section: Discussionsupporting
confidence: 75%
“…Wichmann et al reported that the VMIs at 60 keV significantly improve the contrast noise ratio (CNR), subjective overall image quality, and tumor delineation of head and neck squamous cell carcinoma . According to another report by Lam et al , the difference in CT number between tumor and muscle is the highest on the VMI at 40 keV for HNC . The high quality of image has the potential for improving the accuracy of target/OARs delineation for radiotherapy treatment planning …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…reported 65–75 keV maximizing brain parenchymal image quality in GE Discovery CT750HD DECT scanner with fast‐kVp‐switching mode. For this GE scanner, Lam et al . demonstrated that 65 keV is optimal to achieve best signal‐to‐noise ratio for tissues in head and neck region.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, emerging dual-energy CT techniques have been investigated for head and neck cancer imaging with the potential for improved tumor visualization and characterization. [14][15][16][17][18][19][20][21] In particular, techniques using iodine overlay (IO) images were found useful for distinguishing iodine-enhanced tumors from nonossified cartilage 11,14,19,22 and for having higher specificity than conventional CT, without a deterioration of sensitivity, in particular for the evaluation of thyroid cartilage invasion. 14 Furthermore, interobserver agreement is usually poor for conventional CT and was found to be higher for dual-energy CT. 14,23 These new dualenergy CT techniques have prompted re-evaluations of the diagnostic performance of CT compared with MR imaging in diagnostic fields where MR imaging has been routinely used.…”
mentioning
confidence: 99%